The Influence of Transformational Leadership and Physical Work Environment Mediated by Extrinsic Motivation in Improving Employee Performance at the Regional Office of the Ministry of Law and Human Rights, West Nusa Tenggara - Aryadi, Dedy; Arthur Sitaniapessy; Rismawati (Yayasan Inspirasi Merah Putih Indonesia, 2025)
The purpose of this study is to examine and analyze the influence of transformational leadership and physical work environment on employee performance, mediated by extrinsic motivation, both directly and indirectly, at the Regional Office of the Ministry of Law and Human Rights, West Nusa Tenggara. This research employs a causal approach. The population consists of all employees at the aforementioned Regional Office. The sample is determined using a saturated sampling technique involving 87 employees, with 80 valid responses analyzed. Data collection techniques include documentation, observation, and questionnaires. The data analysis uses a quantitative approach through statistical methods, including Outer Model Analysis, Inner Model Analysis, and Hypothesis Testing. Data processing is conducted using the PLS (Partial Least Square) software. The results show that transformational leadership has a significant direct effect on employee performance, the physical work environment has a significant effect on employee performance, and extrinsic motivation significantly influences employee performance. Additionally, transformational leadership and the physical work environment significantly affect extrinsic motivation. However, extrinsic motivation does not mediate the relationship between transformational leadership and employee performance, nor does it mediate the relationship between the physical work environment and employee performance at the Regional Office of the Ministry of Law and Human Rights, West Nusa Tenggara.